The last devil to die [large type] - Osman, Richard, 1970- (Osman, Richard, 1970- Thursday Murder Club mystery., 2023)
When a dangerous package goes missing on Boxing Day, the Thursday Murder Club, when one of their own is murdered, take on their most deadly opponents yet.